A 5-Year Evaluation of Faculty Use of Practical Within-Course Writing Development Strategies in a DNP Program. Issue 4 (July 2019) - Hampton, Michelle DeCoux
Abstract : Background: Nursing students are underprepared for the rigors of graduate writing. The lack of sufficient writing opportunities and skill development in prelicensure nursing education creates barriers that threaten course and program progression. Approach: This study used a prospective, repeated-measures design to evaluate 5 years of faculty-implemented writing development strategies in a DNP program. Outcomes: Faculty adopted 12 strategies in 10 courses. The strategies addressed skill building in content, construction, format, plagiarism, and citation use. The most frequently used strategies were rubrics, plagiarism detection software, multistep assignments, and examples of well-written papers, all strategies that increased in use over the 5-year study. Conclusions: Graduate faculty interact with students and assess writing development outcomes firsthand. Changes in faculty practices over time can indicate the strategies they consider most valuable for writing development. Abstract : Supplemental digital content is available in the text.